Comparing the Emotional Intelligence between PTSD and non-PTSD Veterans - S. Imani; S. Atari; Sh. Shahidi; V. Sadeghi Firooz Abadi; M. Khanabni; N. Zamani (Afarand Scholarly Publishing Institute, 2015)
Aims: Post-traumatic stress disorder (PTSD) may be caused by a variety of stressful factors, such as presence in a war (as one of the main factors). Based on the conducted studies, persons with higher emotional intelligence are less affected by the stressful events. The aim of this study was to compare emotional intelligence in veterans with PTSD and other veterans. Instrument & Methods: In this causal-comparative study, 120 veterans with PTSD, or chemical injuries, or mutilation, hospitalized in Sadr, Sassan, and Kowsar Medical Centres, as well as normal ex-soldiers, were selected through Available Sampling Method in 2009. The subjects were divided into 4 groups (n=30 per group), including PTSD, Chemical, Mutilation, and Normal. Study tools were Watson's PTSD and Bar-On EQ questionnaires. Data was analyzed in SPSS 19 software using ANOVA and Post-hoc Tukey tests. Findings: There were significant differences in all components of emotional intelligence between the groups (p=0.001). In addition, mean emotional intelligence score of PTSD group was less than other groups.  Conclusion: Emotional intelligence in veterans with PTSD is lower than other veterans.